Development of thick airfoils for outboard sections and investigation into their application for large rotors. Issue 3 (June 2018) - Caboni, Marco; Boorsma, Koen; Kanev, Stoyan
The use of thick airfoils toward the outboard part of horizontal axis wind turbine blades is a promising concept to reduce the cost of wind energy. In fact, thick airfoils have higher area moments of inertia than those of thin airfoils, normally employed toward the outboard part of the blade. Replacing thin airfoils with thicker ones would therefore allow one to improve the structural properties of the blade, reducing the mass needed to ensure its structural integrity. Conventional thick airfoils, however, are generally characterized by worse aerodynamic performance with respect to those of thin airfoils, which make them less attracting for their use toward the outboard part of the blade. The research reported in this paper deals with the development of an optimization system for the aerodynamic design of thick airfoils, aiming to improve their aerodynamic performance, and therefore making them more suitable for their usage toward the outboard part of the blade. In order to determine the effect of the use of thick airfoils towards outboard sections, a blade design incorporating a newly designed 30% thick airfoil is assessed both statically and dynamically. The results showed that mass reduction can be achieved with the use of ad hoc optimized thick airfoils with limited penalty in power production.